The Lviv Variant of Modernism in Literary Criticism (Katarzyna Sadkowska. Lwowska krytyka literacka. 1894-1914. Tendencje i problemy. Warszawa: Wydawnictwo Uniwersytetu Warszawskiego, 2015. 332 P.) - Panek, Sylwia (Porównania, 2016)
abstrakt